Identification of Engine Inertia Parameters and System Dynamic Stiffness via In Situ Method. (11th August 2021) - Xu, Chuanyan; Gong, Xun; Meng, Lixue; Li, Aijuan
Abstract : An in situ method is presented to identify ten engine inertia parameters and system dynamic stiffness from the frequency response functions. The ten engine inertia parameters and system dynamic stiffness are estimated from two distinct steps. The accuracy of the proposed technique is verified by finite element simulation, and then the generality is validated using an engine supported by a specially designed curved bar spring. The locations of the measure points on the results are also carefully investigated. The identification of system dynamic stiffness is validated comparing with the engine with an auxiliary plate, which shows good consistency with the results identified from the study.